2019
DOI: 10.1080/13685538.2019.1678582
|View full text |Cite
|
Sign up to set email alerts
|

Should isoniazid prophylaxis be prescribed to the patients under tumor necrosis factor-alpha antagonists independent of tuberculin skin test?

Abstract: Annakkaya (2020) Should isoniazid prophylaxis be prescribed to the patients under tumor necrosis factor-alpha antagonists independent of tuberculin skin test?, The Aging

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…In another study in a population of 110 patients, 65 (59%) patients with TST ≥5 mm received INH prophylaxis. Two (1.8%) patients developed active TB despite BCG vaccination and received INH prophylaxis 29 . In another study in Turkey, the incidence of TB was 1.1% among patients with anti‐TNF treatment, nearly 23 times higher than the rate in the general population 30 .…”
Section: Discussionmentioning
confidence: 94%
“…In another study in a population of 110 patients, 65 (59%) patients with TST ≥5 mm received INH prophylaxis. Two (1.8%) patients developed active TB despite BCG vaccination and received INH prophylaxis 29 . In another study in Turkey, the incidence of TB was 1.1% among patients with anti‐TNF treatment, nearly 23 times higher than the rate in the general population 30 .…”
Section: Discussionmentioning
confidence: 94%
“…On the contrary, meta-analyses evaluating patients treated with adalimumab, etanercept, infliximab, rituximab, abatacept, and anakinra concluded that the risk of severe infection did not increase (8-10). In the study by Alaşan et al 11 conducted in Türkiye, it was reported that TB developed in 2 cases (1.8%) due to the use of etanercept and infliximab among 110 patients who were under anti-TNF therapy. Since mycobacterial infections have been reported very rarely in patients receiving rituximab, there is no recommendation to screen for latent TB before using rituximab treatment (12).…”
Section: Discussionmentioning
confidence: 99%